Application of stereological methods for the quantification of VCAM-1 and ICAM-1 expression in early stages of rabbit atherogenesis - Nachtigal, Petr; Semecky, Vladimir; Kopecky, Martin; Gojova, Andrea; Solichova, Dagmar; Zdansky, Petr; Zadak, Zdenek (Pathology, research and practice, 2004)
Early stages of atherogenesis are characterized by the overexpression of cell adhesion molecules with the subsequent accumulation of macrophages, smooth muscle cells and proliferation of extracellular matrix in arterial intima. The quantification of atherogenic changes is necessary for the objective evaluation of the atherogenic process. The purpose of this study was to introduce stereological methods that may be used for the quantification of immunohistochemical staining, namely intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). Twenty-four New Zealand White rabbits were subdivided into the three groups. Eighteen rabbits received a 0.4% cholesterol diet for 1, 2 and 3 months, respectively. Stereological principles of the systematic uniform random sampling and the point-counting method were applied for the quantification. Stereological analysis showed that VCAM-1 and ICAM-1 were upregulated during the consumption of high cholesterol diet and that VCAM-1, but not ICAM-1, has a considerable role in the formation of early atherosclerotic lesions. Stereological methods proved to be useful for the quantification of immunohistochemistry and can be used for an objective characterization of atherogenic changes in atherosclerosis.
Keywords: hypercholesterolemie; Aorta, Thoracic; cholesterol dietní; Disease Models, Animal; Intercellular Adhesion Molecule-1; zvířata; imunoenzymatické techniky; králíci; Time Factors; Microscopy; Animals; časové faktory; Hypercholesterolemia; modely nemocí na zvířatech; Rabbits; Arteriosclerosis; mikroskopie; Vascular Cell Adhesion Molecule-1; Cholesterol; Immunoenzyme Techniques; dieta aterogenní; Cholesterol, Dietary; Diet, Atherogenic; Male; Endothelium, Vascular; mezibuněčná adhezivní molekula-1; mužské pohlaví; cholesterol; cévní endotel; arterioskleróza; cévní buněčněadhezivní molekula-1; aorta thoracica